PENGARUH JOB INSECURITY TERHADAP KOMITMEN ORGANISASI SERTA IMPLIKASINYA PADA KINERJA KARYAWAN SELAMA PANDEMI COVID 19 VARIAN OMICRON - Muhammad Ainan; Syamsul Hadi; Nova Widjoyo Aryo Wisanggeni (Universitas Boyolali, 2022)
The Covid 19 pandemic has hit Indonesia since March 2020, in early 2021 a new variant appeared called the Omicron variant, with a very fast spread rate. The deployment of the Omicron Variant led to an increase in Job Insecurity. This study aims to determine the effect of job insecurity on organizational commitment and its implications for performance during the Omicron Variant Covid 19 Pandemic. 100 (one hundred) employees of Hotel Patra Jasa became respondents in this study. Case studies are used to answer the research objectives. Data collection was done by interview with the help of a questionnaire. This study uses path analysis. The results of the study show that during Covid 19 the Omicron Variant the perception of Job Insecurity increased. To reduce the increase in job insecurity, recommendations that can be made by Patra Jasa Convention Hotel management are the need to implement good health protocols so that the Job Insecurity of Patra Jasa Hotel employees does not decrease.